Improving the PET Fabrics Surface using O2/Ar Plasma and Alkaline Treatments at Low Temperature - . A. Elabid1, Amel E; Jing, Zhang (Gezira Journal of Engineering and Applied Sciences, 2018)
Low energy consumption and resource saving have been increasingly adopted in industries to combat resource depletion and to control pollution in the recently. In textile industries the wet chemical processing of textile materials through is adoption of plasma etching. This paper, studied the effect of plasma pre-treatment on alkaline etching on polyethylene terephthalate (PET) fabrics, based on the weight loss after plasma treatment using three different gases argon, oxygen, and oxygen/argon mixture (Ar, O 2 , and O 2 /Ar). It is found that O 2 /Ar plasma treatment and low temperature alkaline treatment gave optimal surface roughness properties of PET fabric. The topographical changes and chemical modification of the fiber surface were analysed using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM).  Then a low alkaline treatment temperature at 85 ° C and 4% concentration was chosen to combine together with plasma treatment at different processes. Also the surface wetting properties were calculated depending on contact angle (cos θ). Water drop spread rapidly and the contact angle was zero on the PET fabric surface by combination treatment and the surface tension between solid-liquid interfacial tensions were 72.72 mJ/m 2 which is equal to the liquid surface tension. It is recommended to study the dyeing properties after improving the surface of PET fabric using plasma/alkaline treatment.